Sacral Neuromodulation for Constipation - Matzel, Klaus; Bittorf, Birgit Renate (Springer Science+Business Media, 2020)
With the increased use of sacral neuromodulation/sacral nerve stimulation (SNM/SNS), it became clear that its effect is not limited to fecal incontinence, but that it may also benefit other pelvic organ disorders. As the technique is minimally invasive and entails a low-risk test phase to identify patients appropriate for chronic stimulation, it has been applied in various functional disorders, constipation being one among them. However, current knowledge indicates that SNM is far less effective for treating constipation than for fecal incontinence. Indeed, in some countries, it is not approved for this purpose. However, recent thinking has suggested that, based on conceptional considerations (mainly its limited invasiveness, low-risk profile, and possibility for test stimulation), it may offer an option in distinct conditions alternative treatments are more invasive and irreversible.
CRIS-Team Scopus Importer:2025-10-16
Keywords: Constipation; Medtronic; Sacral nerve stimulation; Sacral neuromodulation